The Effect of Specialized Exercises Based on Mechanical Principles on Diagonal Attacks from Positions (2) and (4) Among Third-Year Students in Volleyball - Shaker , Rania; Naji , Maram; Ameen , Maher; Kareem , Ahmed (Journal of Physical Education, 2025)
Researchers and specialists in the fields of educational sciences strive to enhance the academic level of their students. Among the most prominent of these sciences is sports science, which encompasses various specializations, curricula, and theories. This has driven professionals in this field to constantly seek the most effective, shortest, and simplest ways to achieve high-quality outcomes through experimentation and practical application. The aim of this research was to develop specialized exercises based on mechanical principles for diagonal attacks from positions (2) and (4) among third-year volleyball students. The study also aimed to determine whether these exercises are more effective than conventional training in influencing the targeted research variables. The researchers employed an experimental approach involving both a control and an experimental group, using pre- and post-tests. Two specific tests were administered, focusing on diagonal attacking skills from positions (2) and (4). The research sample consisted of 12 third-year students from the Department of Physical Education and Sports Sciences at Al-Farahidi University (academic year 2024–2025), who were deliberately selected as top-performing students and divided into two groups (experimental and control), each comprising six students. The SPSS statistical software package was used to analyze the results. After presenting and discussing the results, the study concluded that there was a statistically significant improvement in both groups between the pre- and post-tests. Additionally, a significant difference was found in favor of the experimental group in the post-tests. The researchers recommend the adoption of these exercises due to their significant effectiveness.